Isolation, growth and sporophore development of Ganoderma boninense from oil palm in Malaysia - Ho, Yin Wan; Nawawi, A. (Universiti Pertanian Malaysia, 1986)
A bundant mycelium of G. boninense could be isolated from sporophore tissues cultured on potato dextrose agar (PDA) and from single basidiospore germinating on PDA. The optimum temperature for mycelial growth was between 27-29°C and the best medium was lima bean agar. Sporophore development from mycelial culture was not successful on the various media employed. Studies on the growth of sporophore on infected trunks showed that growth was slow in the first 1-9 weeks, then increased rapidly till the fourteenth week after which growth rate decreased again.